Pengaruh Teori Positivisme Hukum dan Teori Utilitarianisme Hukum Dalam Penegakan Hukum Indonesia - Faradistia Nur Aviva (Jurnal Relasi Publik, 2023)
The influence of the theory or understanding of legal positivism and legal utilitarianism affects law enforcement, especially in Indonesia, so that it is known as positive law. The view of legal positivism in law enforcement is limited to enforcing the sound of laws that emphasize justice in it. Benefit and legal certainty should not be abandoned so that it gives rise to a utilitarianisme view that is more on benefit and legal certainty which is part of law enforcement in Indonesia. That way the author will examine the paradigm between the theory of legal positivism and the theory of legal utilitarianism and how the theory affects law enforcement in Indonesia. These two theories have an influence on law enforcement in Indonesia where legal positivism theory emphasizes justice and legal utilitarianism theory emphasizes legal certainty and expediency. In addition to the benefits of these two theories have weaknesses where the theory of legal positivism is more focused on existing rules while the theory of legal utilitarianism views a psychological approach. So that both of them certainly need the right pull so that the composition of the application in law enforcement in Indonesia can fulfill the principles of law.